PENTAHO SEBAGAI SOLUSI MASALAH PENGOLAHAN DATABASE - Nurtriana Hidayati (Jurnal Transformatika, 2012)
Information is the result of data processing plays an important role in anorganization, especially in decision-making process. Pentaho application of Intelligent Business Products is one of the technologies for collecting, storing, analyzing, and providing access to data to help enterprise users make better business decisions. Pentaho has a function as reporting, analysis, dashboards, data integration (ETL) and data mining. Pentaho is better to manage large and complex data and be able to complete the functional organization.